Specifying Dynamic Distributed Software Architectures - Paula, Virginia C. de; Justo, G. R. Ribeiro; Cunha, P. R. F. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1998: Anais do XII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1998.24016, 1998)
The concept of software architecture is important to the design of complex software systems, as it provides a model of the large scale structural properties of the system. lt is possible to find several formal models to depict static distributed software architecture. Nevertheless, notations for supporting architectural dynamism and evolution are still difficult to find in the literature. We present a formal framework to specify dynamic distributed applications to enable us to specify the dynamic behaviour of reconfigurable systems. This framework will help the designer to check the project suitability.